Body Condition Scores Before and After Calving Modulate Pregnancy Success of Beef Cows in Florida - Philipe Moriel; Vinicius Izquierdo; Joao Vendramini (EDIS)
This publication was developed to help beef cattle producers understand the impacts of cow body condition score (BCS) before and after calving on cow and calf productive performance in Florida. Written by Philipe Moriel, Vinicius Izquierdo, and Joao Vendramini, and published by the UF/IFAS Department of Animal Sciences, February 2025.